Riesgos biológicos en las actividades laborales de los trabajadores del centro de faenamiento del GAD Junín - Vélez Gutiérrez, Raissa Katherine (2022)
The objective of this investigative work was to evaluate the incidence of biological risks in the activities carried out by the workers of the GADM Junín slaughter center for the subsequent elaboration of biosafety protocols. The techniques used were the interview and surveys made to the workers of the slaughterhouse where it was known that 11 workers work and the productive processes that they carry out in two areas that are porcine and bovine. For the assessment of biological risks, the sedimentation method was used and the results obtained in the pig area were 248 CFU for bacteria and 84 CFU for fungi, which means that the level of microbial load was low and the fungal level was very low; In the bovine area, a value of 148 CFU for bacteria and 57 CFU for fungi was obtained, which means that both the microbial and fungal levels were very low altogether. The Biogaval method was also used, the results obtained were 5 and 6, therefore the level of risk of the workers of the slaughter center is below the rates established in this method. In the pig area, the presence of total coliforms and fungi of the genus Penicillium and Cladosporium was evidenced; in the bovine area the presence of total coliforms and bacteria of the genus Salmonella, fungi of the genus Aspergillus and Cephalosporium.